Triaging of patients by general practitioners (GPs) in primary health care settings: a neglected aspect in the health policy & practice in Nepal - Kharal, Puspa Mani (Journal of General Practice and Emergency Medicine of Nepal, 2023)
General Practitioners are the backbones of the primary health care and whole health system around the world. United nation declaration in Alma Ata about primary health care and WHO reinforcement regarding the importance of robust primary health care for universal health coverage are major catalysts to sensitize the government to implement triaging of patients through primary care by general practitioners. Nepal lacks strong primary health care system utilizing general practitioners as frontline health service providers in the community level. This has made people travel a long distance risking high expenses to get basic healthcare. The overcrowding in tertiary care hospitals is a result of improper triaging and referral system. General practitioners in Nepal work in emergency departments of hospitals and medical colleges, do private practices and a small number of GPs work in health departments of Ministry of Health and Population. Proper mobilization of GPs and establishing primary health care system is paramount to achieve equity, efficiency and effectiveness in health services. Current health policies and program must be reviewed and updated based on the evidences from the studies. CME (Continuous Medical Education) was organized in Chitwan for General Practitioners as a regular program of GPEMAN (General Practice and Emergency Medicine Association of Nepal). Participants were asked about primary health care system in Nepal and its opportunities and barriers. Majority of participants 84% (32 out of 38) pointed out that poor health policy and lack of recognition of General Practice for primary health care as first contact physicians by the government are the major challenges and barriers. Evidences will guide government and concerned stakeholders to establish robust primary healthcare system to increase access, efficiency, effectiveness of health service and to reduce out-of-pocket expenditure and disease burden in the community.